2022
DOI: 10.3390/microorganisms10050954
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Biochemical Characterization, and Safety Attributes of Locally Isolated Lactobacillus fermentum from Bubalus bubalis (buffalo) Milk as a Probiotic

Abstract: The demand of functional foods is on the rise, and researchers are trying to develop nutritious dairy products by using well-characterized strains of bacteria. In this study, we identified locally isolated strains of Lactobacillus fermentum from Bubalus bubalis (Nilli Ravi buffalo) milk and evaluated their potential as probiotics in food products like fermented milk. Fifteen Lactobacillus strains were initially isolated, and only four strains (NMCC-2, NMCC-14, NMCC-17, and NMCC-27) were examined for morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 59 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…The adherence property of probiotic strains inhibits or prevents the attachment of pathogenic strains to the epithelial layer of the gut which, in turn, prevents pathogenic activity in the GIT tract of organisms [53,54]. Our results are in accordance with the literature [53,55] which demonstrated that Lactobacilli strains isolated in Islamabad are capable of growing under lysozyme conditions in the range of 96.69-53.45%. The results of gastric conditions are in accordance with the literature; however, according to Tokatlı et al, pancreatin has a negative impact on strain-survival rates which is in contrast to our results [54].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The adherence property of probiotic strains inhibits or prevents the attachment of pathogenic strains to the epithelial layer of the gut which, in turn, prevents pathogenic activity in the GIT tract of organisms [53,54]. Our results are in accordance with the literature [53,55] which demonstrated that Lactobacilli strains isolated in Islamabad are capable of growing under lysozyme conditions in the range of 96.69-53.45%. The results of gastric conditions are in accordance with the literature; however, according to Tokatlı et al, pancreatin has a negative impact on strain-survival rates which is in contrast to our results [54].…”
Section: Discussionsupporting
confidence: 90%
“…Besides, intact LAB cells are known to have antioxidant capabilities; therefore, they are present in the GIT tract. [55,57,58]. While passing through GIT tract, LAB released an antioxidant constituent which was reported as a healthy mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The L. paracasei Zhang strain has good acid resistance and bile salt resistance, strong abilities in immune regulation and antioxidation, and has been widely commercially used as a probiotic food additive and supplement [ 4 ]. Lactic acid bacteria are frequently added during food production, and some of them enter the viable but nonculturable (VBNC) state to maximize their survival when facing unfavorable growth conditions during food processing and fermentation [ 5 , 6 ]. However, the current knowledge of VBNC bacteria has mainly been developed in studies of pathogenic bacteria, and our understanding of the VBNC state of probiotics or bacteria that are used in food is limited [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates, in general, exert a strong influence on the process of cell surface adhesion through carbohydrate-receptor (lectin) or carbohydratecarbohydrate interactions [34,37]. Most carbohydrate molecules (e.g., galactose, lactose, MNS) are used to bind with lectin receptors commonly found in liver cells and also on the bacterial cell surface [38]. MNS-coated MOFs were used to enhance the bactericidal activity of VCM against Staphylococcus aureus-resistant strains in this study.…”
Section: Introductionmentioning
confidence: 99%